An evaluation of an array of viruses and fungi in adult Lebanese patients presenting with various dental infections: A cross-sectional study - Wael Khalil; Hani Abd-Ul-Salam; Abd El Hadi Kanj; Rémi Safi; Mohammad El-Harakeh; Mazen Kurban; Elias A Rahal; Ghassan M Matar (Journal of Infection in Developing Countries)
Introduction: The role of bacteria in the pathogenesis of periodontitis, pericoronitis, and periapical infections has been well-established. However, the variation in the severity and prognosis of these lesions could suggest a potential role of other microorganisms, such as viruses and fungi. This study aims to evaluate the presence of adenovirus, human papillomavirus-16, Epstein-Barr virus, Candida, and non-Candida fungi in these infections.